Effect of different carbon sources on the biosynthesis of polyunsaturated fatty acids of α-linolenic acid family in culture of minimal deviation hepatoma 7288 c cells - Tacconi de Alaniz, María Josefa (1976)
The effect of three different carbon sources on the biosynthesis of polyunsaturated fatty acids of the α-linolenic acid series was investigated in hepatoma tissue culture (HTC) cells. Alpha linolenic acid was converted to higher homologs by a desaturating route that synthetized mainly 18:4 (Δ6, 9, 12, 15), 20:4 (Δ8, 11, 14, 17) and 20:5 (Δ5, 8, 11, 14, 17) and an elongating route that produced 20:3 (Δ11, 14, 17) and 20:4 (Δ5, 11, 14, 17) acids. ‘Fasting’ decreased both biosynthetic routes whereas glucose reactivated only the elongating pathway. Lactalbumin hydrolysate enhanced significantly only the desaturating route whereas glycerol was inactive. Glucose and aminoacids increased similarly the incorporation of labeledα linolenic acid in the cells. The results are independent of hormonal effects.